“Good Will Toward Men” (Luke 2 14) - Ropes, James Hardy (Harvard theological review, 1917)
Professor Adolf von Harnack in the Sitzungsberichte of the Berlin Academy for December 9, 1915 (pages 854–875) has discussed afresh in his characteristically interesting and instructive fashion the textual criticism and meaning of the angels' song in Luke 2 14. After a full exposition of the evidence and an investigation of the rare word εὐδοκία, he decides for the following text:Δόξα ἐν ὑΨίστοις ϑεῷ καὶ ἐπὶ γῆςΕἰρήνη ἀνϑρώποις εὐδοκίας,which he translates:“Glory in the highest to God and on earthPeace to men of (His) gracious will.”This form of the Greek text is in the second line substantially that on which the English Revised Version rests (“men in whom he is well pleased”); but Harnack, following Origen, connects εὐδοκίας not with ἀνϑρώποις but, by a somewhat harsh hyperbaton, with εἰρήνη, and interprets: “Peace is now given to men—no ordinary peace but the peace of His gracious will.”Harnack's argument, which contains much valuable discussion on various aspects of the verse, need not be here repeated. But two of the points which he makes, and in regard to which his reasoning is convincing, deserve notice; for although at first sight they might appear to occupy but a modest place among his results, in reality they seem to offer the key to the serious textual problem of the passage, and so lead to a translation and interpretation quite different from Harnack's. They may be stated thus:(1) With the reading εὐδοκίας, the song is a distich, of which the first line must be taken to include the words ἐπὶ γῆς and the second to begin with εἰρήνη.(2) ἀνϑρώποις εὐδοκίας is a phrase wholly unexampled and in itself full of difficulty. For εὐδοκία means “God's gracious will.” It refers to His purpose, His choice, not to His approval or satisfaction with man's performance; and it looks to the future, to grace, to the hope of a needy world, not to the past, to man's merit, or even to the inherent worth of human nature.